(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To reassess the current epidemiological characteristics of malaria and analyze the difficulties in malaria elimination and prevention of malaria recurrence in the region. Methods of research and literature review: Retrospective descriptive review of malaria data. Analysis of malaria patient data, severe malaria, malaria mortality, epidemiological assessment, malaria parasites, and malaria insects. Results: The malaria situation has decreased, no malaria outbreaks have occurred, and the distribution of cases is even throughout the year. There are more than 20 Anopheles species (3 main malaria vectors). Many difficulties and challenges remain in malaria prevention and elimination, such as the malaria control system, drug-resistant malaria, chemical-resistant mosquitoes, and the risk of malaria transmission from monkeys to humans. Conclusion: The malaria situation in the region is trending downwards across all indicators. Local malaria cases are mainly concentrated in the former Binh Phuoc province. By 2025, By 2025, 19/20 former provinces/cities have met the criteria for malaria elimination. Difficulties and challenges for malaria prevention and elimination, and prevention of malaria re-establishment at present and in the future such as shortage of resources, drug-resistant malaria, insecticide-resistant malaria mosquitoes, high risk of malaria from monkeys (P. knowlesi) to humans, imported malaria from Africa and some malaria endemic areas within and outside the country are always present.